FEATURES DELINEATION AND USE OF SPECIALLY PROTECTED THE CASPIAN LOWLAND THE REPUBLIC OF DAGHESTAN - Z. A. Kurbanova (Вестник Дагестанского государственного технического университета: Технические науки)
Questions of delimitation of state property on specially protected areas land of the Caspian lowland in Daghestan need further study. It is Requires the definition of the status of land of recreational zones of the coast of the Caspian sea, including coastal and border strips, legal and logical resolution of the millet for the management of these lands as Federal property. It is Necessary to accelerate the work on the delimitation of the remaining areas of land in this zone, to take inventory, to put these lands on cadastral registration and to sign lease agreements with businesses on these lands.